2017
DOI: 10.5539/jmbr.v7n1p80
|View full text |Cite
|
Sign up to set email alerts
|

From 48 to 46 Chromosomes: Origin of Modern Man

Abstract: It is old-established that the chromosome number in the chimpanzee, gorilla and orangutan was 48 and not 46 as in man. However, cause and effect of such chromosome rearrangement is unknown. A hypothesis has been proposed that natural selection caused merger of two pairs of autosomes into one chromosome. In the changed climate of the East Africa individuals with less amount of chromosomal Q-heterochromatin regions (Q-HRs) in genome were the most adapted. Two pairs of acrocentrics in the genome the common ancest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In particular, we have shown that according to the distribution pattern of chromosomal Q-HRs on seven Q-polymorphic autosomes (3, 4, 13-15, 21 and 22), the populations surveyed by us from different regions of Eurasia and Africa do not differ significantly [50]. This may indicate that modern humans may have originated from a single ancestral population [13][14][15][16][17][18][19][20][21][22]. It would be desirable to repeat similar comparative cytogenetic studies on different populations living on other continents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we have shown that according to the distribution pattern of chromosomal Q-HRs on seven Q-polymorphic autosomes (3, 4, 13-15, 21 and 22), the populations surveyed by us from different regions of Eurasia and Africa do not differ significantly [50]. This may indicate that modern humans may have originated from a single ancestral population [13][14][15][16][17][18][19][20][21][22]. It would be desirable to repeat similar comparative cytogenetic studies on different populations living on other continents.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the main harmful environmental factor turned out to be cold, which has been haunting and haunting man to this day, because Homo s. sapiens was and remained a single tropical biological species. This problem, as we believe, was solved at the genome level, in this case by changing the number of chromosomes (from 48 to 46), the amount and localization of their heterochromatin regions [22,23]. Some additional clarifications may be required here.…”
Section: Interpretationsmentioning
confidence: 97%
See 1 more Smart Citation